The Role of Gonadotropins and Growth Factor in Regulating Ras During Maturation in Cumulus–Oocyte Complexes of Pigs - Eunju Seok; Minyoung Son; Seunghyung Lee; Hee-Tae Cheong; Sang-Hee Lee (Animals, 2025)
Oocytes and cumulus cells undergo meiotic resumption and proliferation via gonadotropins and growth factors during maturation, and various small G proteins are activated when COCs undergo physiological changes. This study investigated the influence of gonadotropins and growth factors on Ras and its GTPases during porcine COC maturation. Unmatured COCs were treated with FSH, LH, or EGF for 44 h. The mRNA expression levels of the Ras subfamily (H-Ras, K-Ras, N-Ras, and R-Ras), its GTPases (RASA1 and SOS1), and proliferation factors (ERK, CCNB1, and Cdc2) were analyzed using RT-PCR. In contrast to other Ras subfamilies, R-Ras expression is upregulated during COC maturation. We evaluated the effects of FSH, LH, and EGF at various concentrations that most effectively regulated the expression of R-Ras and GTPases. The results demonstrated that 0.5 µg/mL FSH, 10 IU/mL human chorionic gonadotropin (hCG), and 10 ng/mL EGF effectively enhanced R-Ras expression and cell proliferation. FSH supplementation during porcine COC maturation significantly upregulated R-Ras and ERK expression, independent of LH and EGF, and downregulated Cdc2 expression. These results indicated that FSH regulates R-Ras expression, thereby promoting cell proliferation during COC maturation. These results provide fundamental knowledge for understanding the role of Ras and its family members in the development of follicular environments in pigs.